Making sense of the mind. - Galligan, Edward L. (Sewanee Review)
Focuses on Gerald M. Edelman's theory of how the mind and the nervous system work. Theory of Neural Group Selection; Human consciousness as the product of the evolutionary development of the human brain; Rejection of Noam Chomsky's theory of language; Distinction between systems of instruction and systems of selection.